HUMAN RESOURCE MANAGEMENT IN UKRAINIAN BANKS: A STRATEGIC PERSPECTIVE IN THE CONTEXT OF INCREASED ACTIVITY IN THE RETAIL BANKING SEGMENT - Venkatachalam, V. Balaji; Kramar, Viktoriya (Journal of European Economy, 2018)
Banking is a heavily capitalized sector whose investments consist essentially of employees to such an extent that the transformation required can only be affected over time. Strategically, if Ukrainian banks are to be successful, in the near future they will have to redefine the principles of Human Resource Management (HRM) and make it of top priorities. HRM practices are most effective when matched with the strategies of organization. By adapting high-performance workplace practices, banks in Ukraine can create capabilities that will add value to their operations.